ASSESSMENT OF THE GENERAL CONDITION AND QUALITY OF LIFE OF WOMEN POST-PRODUCTIVE AGE, WHO SUFFERED FROM COVID-19 ASYMPTOMATICALLY, AND 12 MONTHS AFTER THE MODERATE SEVERE FORM OF THE DISEASE - Khusainova Munira Alisherovna, Yarmatov Suvon Totlibayevich, Makhmudova Khanuza Davranovna, Khaydarova Zarrina Erkinovna (Journals Park Publishing, 2022)
Assessment of the general condition, laboratory parameters, and quality of life of post-productive women after the asymptomatic course of COVID-19 and 12 months after the moderate course of the disease.
Keywords: COVID-19, quality of life, women, post-productive period